Dermis mechanical behaviour after different cell removal treatments. Issue 9 (September 2016) - Terzini, Mara; Bignardi, Cristina; Castagnoli, Carlotta; Cambieri, Irene; Zanetti, Elisabetta M.; Audenino, Alberto L.
Highlights: The mechanical properties of the decellularized skin have been compared to the native dermis ones. True stress/strain curves have been estimated through real-time photogrammetry. The optimal decellularization treatment kind and duration has been identified. The ultimate tensile strength can be heavily underestimated considering engineering curves. Values obtained from engineering stress/strain curves remain useful for comparative analyses. Abstract: Human acellular dermal matrices (HADMs) are used in reconstructive surgery as scaffolds promoting autologous tissue regeneration. Critical to the HADM ability to remodel and integrate into the host tissue is the removal of cells while maintaining an intact extracellular architecture. The objective of this work is to develop a methodology to analyse the mechanical properties of HADMs after decellularization to identify its ideal form of treatment and its duration. Two different decellularization techniques were used as a benchmark: the first is a well-established technique (incubation in NaOH for 1–7 weeks), and the second is an innovative technique developed by this research group (incubation in DMEM (Dulbecco's modified Eagle medium) for 1–7 weeks). After decellularization, the specimens underwent uniaxial tensile tests, and experimental data were represented with stress strain curves, calculating both engineering and true values. Mechanical tests have led to the identification of the optimal method (NaOH or DMEM) and duration for the decellularization treatment; differences between engineering and true values can reach 84%, but the engineering values remain useful to make comparisons, providing reliable indications with a simpler experimental set up and data processing. Graphical abstract: